Behind the Decrease of Liver Stiffness After Successful Hepatitis C Virus Eradication with Direct-Acting Antiviral Agents - Mauro Giuffrè; Mauro Giuffrè; Flora Masutti; Ivo Maria Crosato; Roberto Luzzati; Roberto Luzzati; Lory Saveria Crocè; Lory Saveria Crocè; Lory Saveria Crocè (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Giuffrè M, Masutti F, Maria Crosato I, Luzzati R, Saveria Crocè L. Behind the decrease of liver stiffness after successful hepatitis c virus eradication with direct-acting antiviral agents. Turk J Gastroenterol. 2022;33(2):169-170.